Lehninger principles of biochemisty - Nelson, David L.; Cox, Michael M. Professor of Biochemistry; Hoskins, Aaron A. Associate Professor of Biochemistry (New York Macmillan International, 2021)
Lehninger Principles of Biochemistry earned acclaim for its presentation and organisation of complex concepts and connections, anchored in the principles of biochemistry. This legacy continues in the eight edition with a new framework that highlights the principles and supports student learning
1. Foundations of biochemistry -- 2. Water, the solvent of life -- 3. Amino acids, peptides, and proteins -- 4. The three-dimensional structure of proteins -- 5. Protein function -- 6. Enzymes -- 7. Carbohydrates and glycobiology -- 8. Nucleotides and nucleic acids -- 9. DNA-based information technologies -- 10. Lipids -- 11. Biological membranes and transport -- 12. Biomechanical signaling -- 13. Introduction to metabolism -- 14. Glycolysis, Gluconeogenesis, and the pentose phosphate pathway -- 15. The metabolism of glycogen in animals -- 16. The citric acid cycle -- 17. Fatty acid catabolism -- 18. Amino acid oxidation and the production of urea -- 19. Oxidative phosphorylation -- 20. Photosynthesis and carbohydrate synthesis in plants -- 21. Lipid biosynthesis -- 22. Biosynthesis of amino acids, nucleotides, and related molecules -- 23. Hormonal regulation and integration of mammalian metabolism -- 24. Genes and chromosomes -- 25. DNA metabolism -- 26. RNA metabolism -- 27. Protein metabolism -- 28. Regulation of gene expression
Includes bibliographical reference and index
Keywords: Biochemistry